Evaluation of Ginsenosides and Their Derivatives From Panax ginseng as Aromatase Inhibitors for Breast Cancer Treatment—An in silico study. - Madhan, Jayasri Gokila; Sekaran, Surya; Akshaya, Rajeswari Nambirajan; Venkatesan, Khavyanjali; Kirupanandasamy, Kavin; Vijayakumar, Kiruthika; Jenifer, Nancy; Paul, Benedict Christopher; Tyagi, Abhishek (BioMed Research International, 2026)
Breast cancer, particularly estrogen receptor‐positive subtypes, is a leading cause of cancer‐related mortality worldwide. Aromatase inhibitors, which target estrogen biosynthesis, are a cornerstone of therapeutic intervention. Panax ginseng, a widely recognized medicinal herb, contains bioactive compounds known as ginsenosides, which possess various pharmacological activities, including anticancer properties. This study is aimed at evaluating the potential of ginsenosides and their derivatives from Panax ginseng as aromatase inhibitors for breast cancer treatment through in silico methods. Molecular docking studies were conducted to investigate the binding affinities of ginsenosides to aromatase, a critical enzyme in estrogen biosynthesis. The results indicated that several ginsenosides exhibited strong binding affinities, with Protopanaxadiol demonstrating the highest affinity (−10.0 kcal/mol) and an estimated Ki value of 46.77 nM. Molecular dynamics simulations confirmed the stability of the protopanaxadiol‐aromatase complex, highlighting its consistent binding interactions and minimal structural fluctuations. Pharmacokinetic evaluations suggested that most ginsenosides adhered to drug‐likeness criteria, although certain derivatives showed deviations that may affect bioavailability. However, toxicity predictions revealed a predominantly low toxicity profile, with some concerns related to hepatotoxicity and mutagenicity for specific compounds. The findings from this study highlight the potential of ginsenosides and their derivatives as viable candidates and protopanaxadiol as a promising lead compound for further experimental investigation as aromatase inhibitors, offering a promising alternative or adjunct to conventional breast cancer therapies.